2021
DOI: 10.1002/jia2.25686
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing HIV retesting during pregnancy and postpartum in four countries: a cost‐effectiveness analysis

Abstract: Introduction: HIV retesting during late pregnancy and breastfeeding can help detect new maternal infections and prevent mother-to-child HIV transmission (MTCT), but the optimal timing and cost-effectiveness of maternal retesting remain uncertain. Methods: We constructed deterministic models to assess the health and economic impact of maternal HIV retesting on a hypothetical population of pregnant women, following initial testing in pregnancy, on MTCT in four countries: South Africa and Kenya (high/intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…Recent modeling studies in Kenya suggest that maternal retesting is cost-effective when retesting occurs in late pregnancy with catch-up testing at delivery or 6 weeks postpartum for women without antenatal retesting; however, retesting at 2 or more time points had limited utility and was not cost-effective. 20 In our study, HIV incidence during pregnancy and postpartum was 0.50/100 PY, which was lower than other recent studies of HIV incidence in Kenya and other parts of sub-Saharan Africa, 2,21-24 and may reflect declines in HIV incidence in Kenya. As scale-up of implementation a All women enrolled in the cross-sectional and programmatic abstraction only studies at all sites; retesting conducted as part of the cross-sectional study procedures was omitted.…”
Section: Discussioncontrasting
confidence: 81%
“…Recent modeling studies in Kenya suggest that maternal retesting is cost-effective when retesting occurs in late pregnancy with catch-up testing at delivery or 6 weeks postpartum for women without antenatal retesting; however, retesting at 2 or more time points had limited utility and was not cost-effective. 20 In our study, HIV incidence during pregnancy and postpartum was 0.50/100 PY, which was lower than other recent studies of HIV incidence in Kenya and other parts of sub-Saharan Africa, 2,21-24 and may reflect declines in HIV incidence in Kenya. As scale-up of implementation a All women enrolled in the cross-sectional and programmatic abstraction only studies at all sites; retesting conducted as part of the cross-sectional study procedures was omitted.…”
Section: Discussioncontrasting
confidence: 81%
“…26–28 Nevertheless, more frequent HIV testing and faster scale-up of ART alone is unlikely to be sufficient to reach virtual elimination of HIV. 29 Other modeling efforts have suggested that even universal ART coverage by 6 months following infection can leave notable levels of residual incidence from transmission during the acute infection period. 30 Therefore, further scaling up HIV prevention services, facilitated through increased HIV testing, will have an impact on both HIV prevention and mortality reduction.…”
Section: Discussionmentioning
confidence: 99%
“…cRCT outcome data and the micro-costing data will be used to estimate the average cost per FP user. An existing MTCT Markov model used to measure health impact of maternal HIV retesting in Kenya, including upstream elements related to pregnancy risk and unintended pregnancy [ 46 , 47 ] will be adapted to include estimates of unintended pregnancies including unmet need for FP among WLWH (from Mobile WACh Empower trial), vertical transmission rates in Kenya, current maternal ART and infant ARV regimens, and contraceptive failure rates from LMICs. Model parameters will include time since HIV diagnosis, ART use, ART adherence, HIV viral suppression, breastfeeding status, and infant ARV use.…”
Section: Methodsmentioning
confidence: 99%